2002
DOI: 10.1086/343808
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriCagA Seropositivity and Gastric Carcinoma Risk in a Japanese American Population

Abstract: Helicobacter pylori colonization is associated with gastric cancer, but whether and to what extent the risk is greater for strains with the cagA gene than for those without needs to be determined. Between 1967 and 1977, 9963 Japanese American men were recruited and examined. By 1996, incident cases of gastric carcinoma of the distal stomach had been diagnosed in 261 men. Stored serum samples from these case patients and 261 age-matched control subjects were tested for immunoglobulin G antibodies to H. pylori a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 43 publications
4
79
2
2
Order By: Relevance
“…pylori gastric colonization stimulates inflammatory, erosive, and neoplastic processes (62). That H. pylori strains lacking cagA induce less inflammation (63), and are less commonly associated with both peptic ulceration, (19,64) and gastric adenocarcinoma (18,64), suggests that inflammation and these processes may be linked. Although the mechanisms by which H. pylori induces ulceration are not well understood, the ability of H. pylori to stimulate gastric cell secretion of various MMPs (24 -26, 65-68) suggests that H. pylori induces stromal destruction and host cell de-adherence via MMP-mediated degradation of collagens and other connective tissue proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pylori gastric colonization stimulates inflammatory, erosive, and neoplastic processes (62). That H. pylori strains lacking cagA induce less inflammation (63), and are less commonly associated with both peptic ulceration, (19,64) and gastric adenocarcinoma (18,64), suggests that inflammation and these processes may be linked. Although the mechanisms by which H. pylori induces ulceration are not well understood, the ability of H. pylori to stimulate gastric cell secretion of various MMPs (24 -26, 65-68) suggests that H. pylori induces stromal destruction and host cell de-adherence via MMP-mediated degradation of collagens and other connective tissue proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Other cagA and/or cagI-related effects include increased host cell apoptosis (14), nuclear factor-B activation (15), and secretion of pro-inflammatory chemokines such as interleukin-6 and -8 (16,17). Compared with cagA Ϫ strains, cagA ϩ strains are associated with increased risk of peptic ulcer disease and carcinogenesis (18,19).…”
mentioning
confidence: 99%
“…However, it has not been elucidated whether the magnitude of immune response to CagA is associated with risk for gastric cancer. Thus far, only one study investigated the association between CagA antibody titer and gastric cancer in a prospective way (16) and another study investigated the issue in a retrospective way (17). Interestingly, a low titer of CagA IgG antibody was associated with high risk for gastric cancer in both studies, although it was not clear whether the observed phenomenon was reproducible in other prospective and retrospective studies.…”
Section: Introductionmentioning
confidence: 97%
“…Helicobacter pylori frequently colonizes the human stomach (1), and hosts infected by cagA-positive strains are at increased risk of gastric cancer and peptic ulceration (2)(3)(4)(5)(6)(7)(8)(9)(10). H. pylori injects the CagA protein into host gastric epithelial cells via a type IV secretion system (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%